A Numerical Analysis of the Influence of Oxygen and Glucose in Healthy and Tumour Cells - Maria Inês Barbosa; Jorge Belinha; Renato Natal Jorge; Ana Xavier de Carvalho (Applied Sciences, 2024)
Cancer is widely regarded as a critical health issue in modern society. Tumour cells are usually associated with abnormal proliferation that disrupts the normal behaviour of the body. All cells depend on the availability of oxygen and nutrients present in the extracellular environment, which can enhance or decrease their ability to proliferate. Therefore, to comprehend the influence of these factors, it is helpful to understand the proliferation process of both healthy and tumour cells. Computational models are powerful tools used to study biomedical problems, and several models have been presented in the literature. Different numerical methods have been proposed to solve these models. Among them, meshless methods can be highlighted, as they are used to solve complex problems with accurate results. However, in the case of cell proliferation, this is still an area that has not yet been fully explored. The aim of this work is to implement and study the influence of oxygen and glucose during the proliferation of healthy and tumour cells using a novel algorithm. This is an iterative discrete algorithm that employs a meshless numerical and uses a new phenomenological law to describe cell growth. In the end, the algorithm was capable of generating satisfactory results, in accordance with the literature.